Role of family medicine in undergraduate medical education - (:unkn) unknown (My University, 2003)
Family physicians in medical education can enhance clinical learning of the following; knowledge and awareness of the principles and application of health promotion and disease prevention, awareness of psycho-social, cultural, familial, and socioeconomic aspects of medical problems as they relate to patient management, role of the family physician within the health care delivery system and understanding of general practice in real life experience. All these objectives are relevant with the global aim of optimal primary care. As medical care is changed by proper medical education, it will be necessary to utilize family medicine and family physicians in undergraduate medical education as role models for students. In a medical education system that only promotes post graduate medical education on specialties but not general medicine, it is obvious that the student will not be motivated about primary care or the health needs of the community. In order to inject that kind of perspective to the medical students, changing or at least integrating, community- based education or primary care- based rotations with family physicians as mentors, is not only an international but also a national requirement because primary care is what most of the graduates will be dealing with.
Keywords: Family medicine; National needs; Undergraduate Medical examination